Acute onset of ulcerative colitis during chemoradiotherapy for anaplastic lymphoma kinase‐positive lung adenocarcinoma. Issue 2 (22nd December 2017) - Fujita, Kohei; Mizumoto, Yoshinori; Moriyoshi, Koki; Araki, Norio; Mio, Tadashi
Abstract : We report a case of acute onset of ulcerative colitis (UC) during chemoradiotherapy in a patient with anaplastic lymphoma kinase (ALK)‐positive lung adenocarcinoma. A 46‐year‐old male patient with an abnormal chest shadow was referred to our hospital. He was diagnosed with lung adenocarcinoma, clinical stage T1aN3M0 and stage IIIB. Concurrent chemoradiotherapy was selected for his initial therapy. After two cycles of cisplatin and vinorelbine administration, he experienced persistent diarrhoea and anorexia. Findings of the colonoscopy revealed a pancolitis type of UC. After discontinuation of chemotherapy, oral administration of mesalazine was initiated. The development of UC during chemotherapy is very rare and only a few case reports have been published. Although adverse events are rare, it is very important to assess the colitis precisely by performing a colonoscopy when protracted abdominal pain is experienced by the patient, along with diarrhoea or bloody stool during chemotherapy. Abstract : Cytotoxic chemotherapy can cause various adverse effects involving the mucosa of the gastrointestinal tract. Although drug‐induced enterocolitis is a common phenomenon, ulcerative colitis (UC) is a very rare condition and only a few cases have been previously reported. Here, we discuss a case of acute onset UC during chemoradiotherapy in a patient with anaplastic lymphoma kinase‐positive non‐small cell lung cancer.